The Timing of Nitrogen Addition Impacts Yeast Genes Expression and the Production of Aroma Compounds During Wine Fermentation - Godillot, Joséphine; Sanchez, Isabelle; Perez, Marc; Picou, Christian; Galeote, Virginie; Sablayrolles, Jean-Marie; Farines, Vincent; Mouret, Jean-Roch (Frontiers in Microbiology, 2022)
Among the different compounds present in the must, nitrogen is an essential nutrient for the management of fermentation kinetics but also plays an important role in the synthesis of fermentative aromas. To address the problems related to nitrogen deficiencies, nitrogen additions during alcoholic fermentation have been implemented. The consequences of such additions on the main reaction are well known. However, their impact on aromas synthesis is still poorly understood. So, the main objective of this study was to determine the impact of nitrogen addition during the stationary phase on both the fermentation kinetics and aroma synthesis. To reach this goal, we used a transdisciplinary approach combining statistical modeling (Box-Behnken design and response surface modeling) and gene expression study (transcriptomic analysis). Our results indicated that nitrogen metabolism, central carbon metabolism, fermentation kinetics and aroma production were significantly impacted by nitrogen addition. The most remarkable point was the different regulation of the bioconversion of higher alcohols into acetate esters on one hand and of fatty acids into ethyl esters on the other hand. We highlighted that the conversion of higher alcohols into acetate esters was maximum when nitrogen was added at the beginning of the stationary phase. Conversely, the highest conversion of acids into ethyl esters was reached when nitrogen was added close to the end of the stationary phase. Moreover, even if the key element in the production of these two ester families appeared to be the enzymatic activity responsible for their production, rather than the availability of the corresponding precursors, these enzymatic activities were differently regulated. For acetate esters, the regulation occurred at gene level: the ATF2 gene was overexpressed following nitrogen addition during the stationary phase. On the opposite, no induction of gene expression was noted for ethyl esters; it seemed that there was an allosteric regulation.